THE ADVENTIST EMERGING ADULT AND THEIR QUEST FOR IDENTITY: A HERMENEUTIC PHENOMENOLOGICAL STUDY - Sarempaa, Istiarti Berci; Lovanomena, Zandritiana; Tornalejo, Adlai Wilfred; Kasingku, Blessy Pricilla; Ang, Charmaine Gayle Catolico (12th International Scholars Conference 2025, 2026)
Emerging Adult (EA), aged 18–25, is a transitional phase in life during which individuals explore more of their identity. This stage is characterized by a process of retrospection and introspection, where they feel “in-between” adolescence and adulthood. During this time, the EA frequently reevaluates their identity and purpose in life. Those who are born and raised in the Seventh-day Adventist homes are not an exception. They encounter challenges as they navigate the tension between their faith-based upbringing and the societal norms of the world. They wrestle with the pressure to compromise their distinctive beliefs and call to stand apart. The complex interplay between cultural assimilation and religious beliefs can potentially create a crisis of identity among Adventist youth. To date, limited empirical research has been conducted on the lived experiences of EAs from Adventist backgrounds who are studying at non-Adventist institutions in the Philippines. This study aimed to explore the narratives of EAs to understand how their unique upbringing shapes their identity, sense of belonging, and purpose. This study utilized hermeneutic phenomenology to explore the lived experience of born-Adventist individuals within Seventh-Day Adventist Churches in Cavite, Philippines. The data were collected through phenomenological interviews following Moustakas’ (1994) interview framework. The data was analyzed using Van Manen’s (1990) lifeworld elements: spatiality, corporeality, temporality, rationality, and materiality. This study concluded with the statement of the essence of the lived experiences of the born-Adventist Emerging Adult and their quest for identity.